Born to Be Wild: Evaluating the Zoo-Based Regent Honeyeater Breed for Release Program to Optimise Individual Success and Conservation Outcomes in the Wild - Tripovich, Joy S.; Popovic, Gordana; Elphinstone, Andrew; Ingwersen, Dean; Johnson, Glen; Schmelitschek, Emily; Wilkin, David; Taylor, Gemma; Pitcher, Benjamin J. (Frontiers in Conservation Science, 2021)
Evaluating the effectiveness of captive breeding programs is central to improving conservation outcomes in released animals. However, few studies have assessed the impact of the strategies and trade-offs involved in husbandry decisions and the selection of traits on the success of breeding programs. This study evaluated a range of husbandry features including an animal’s environment, health, and traits of the released individual and its parents involved in the zoo-based Regent Honeyeater breed for release program to optimise individual reproductive success and survivability, leading to improved conservation outcomes in the wild. We analysed 285 birds using a penalised Cox proportional hazard model to assess survival and an ordinal logistic model to evaluate the reproductive success of zoo bred birds released to the wild. Key features identified by the study highlight the importance of having parents that are successful breeders and parents that have an overall higher lifetime reproductive output. However, there were associated quantity-quality trade-offs, as the success of young (i.e., released birds) produced by parents was negatively associated to the number of clutches per year (where one clutch per year was found optimal). The study demonstrated the importance of considering the parental effects on the traits of its offspring beyond its pedigree information and found there was an associated decline in fitness of its offspring with older fathers. Song tutoring using wild Regent Honeyeaters was also important for increased survival post release. Other important factors are discussed within the review. In general, the study recommended that a multi-faceted approach in the assessment and evaluation of the captive breeding program, to identify markers that will improve conservation outcomes of future releases.